[Kitab Rahasia Hari dan Bintang]: ‘Ilm al-Nujūm ‘inda al-Muslimīn min Qabīlah Sasak - Suprapto, Suprapto (Studia Islamika, 2014)
The manuscript that became the study of this article is the text Kitab Rahasia Hari dan Bintang (The Book on the Mysteries of Days and Stars) which originated from the island of Lombok, in the province of Nusa Tenggara Barat. A part of the Sasak community still uses the contents of the text in their daily lives. Among the important uses of this text is for starting important activities such as building a house, determining the day of a wedding, sailing, trading and also in starting the planting season. The Sasak community uses the calculation of the days in the manuscript that, in local terminology, is often called diwase. Aside from that, the presence of this manuscript, written in the Arabic alphabet pegon, also explains many important things about the transmission of Islamic knowledge from its centre in the Middle East to the archipelago. The transmission process for Islamic knowledge in the archipelago did not only happen in the three main fields of fiqh, kalām, and taṣawwuf, but also in the field of Islamic astrological knowledge which acculturated with local culture.DOI: 10.15408/sdi.v19i3.358